African leadership powerful paradigms for the 21st century - Elkington, Rob; Ngunjiri, Faith Wambura 1973-; Burgess, Gloria J.; Majola, Xoliswa; Schwella, Erwin; De Klerk, Nico (Emerald Publishing, 2023)
African Leadershipis an edited collection enriched by the people who have lived and experienced indigenous leadership first-hand, demonstrating how African leadership is distinctive from usual Western hegemonic paradigms
Keywords: Leadership / Africa; Politik; Wirtschaft; Gesundheitswesen; Führung; Afrika; Aufsatzsammlung